PENGARUH PENANAMAN MODAL ASING (PMA), PENANAMAN MODAL DALAM NEGERI (PMDN), KUALITAS SUMBERDAYA MANUSIA (SDM), DAN TINGKAT PARTISIPASI ANGKATAN KERJA (TPAK) TERHADAP PEREKONOMIAN DI INDONESIA - Nilma Dely; Syamsul Amar; Alpon Satrianto (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to determine and analyze the effect of Foreign Investment (PMA), Domestic Investment (PMDN) on Human Resource Quality (HR) and Labor Force Participation Rate (TPAK) on the Economy in Indonesia, where the quality of human resources is measured using the average length school residents aged 15 years and over. This type of research is descriptive and associative research, namely research that describes the research variable and finds the presence or absence of influence between independent variables and dependent variables. The types of data in this study are secondary data and panel data from 2012-2016 per Province in Indonesia. Data analysis used is descriptive analysis and inductive analysis. In inductive analysis there are several tests, namely: Panel Regression Model, Classical Assumption Test, t Test. The results of this study indicate that (1) Foreign investment (PMA) has a positive and significant effect on the economy in Indonesia, (2) domestic investment (PMDN) has a negative and not significant effect on the economy in Indonesia, (3) the quality of human resources has a positive effect and significant to the economy in Indonesia, (4) the level of labor force participation (TPAK) has a positive and significant effect on the economy in Indonesia. By using α = 5%.